1984
DOI: 10.1037/0022-0167.31.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Component analysis of occupational stress inoculation applied to registered nurses in an acute care hospital setting.

Abstract: The stress inoculation paradigm (SI), which consists of education (Ed), coping skills training (CS), and exposure to simulated stressors (Ex), was applied to the occupational stress experienced by nurses. Occupational stress was operationally defined in terms of 13 dependent measures reflecting problem areas summarized by the acronym Re ACT (retrograde complaints, assertiveness deficits, competency concerns, and time stress). ReACT also stood for the ingredients of the CS component (relaxation training, assert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 34 publications
3
45
0
4
Order By: Relevance
“…We found that the personal accomplishment and the two communication skills such as "accepting valid criticisms" and "negotiation" of the intervention group had improved significantly five months after the training as compared with that of the reference. Our results implied that communication skill Only a few studies have investigated the relationship between communication skill and burnout of health professionals including nurses 17,18) . We studied the relationship between burnout and communication skill training, especially AsT, among Japanese hospital nurses to improve the mental health of human service workers.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…We found that the personal accomplishment and the two communication skills such as "accepting valid criticisms" and "negotiation" of the intervention group had improved significantly five months after the training as compared with that of the reference. Our results implied that communication skill Only a few studies have investigated the relationship between communication skill and burnout of health professionals including nurses 17,18) . We studied the relationship between burnout and communication skill training, especially AsT, among Japanese hospital nurses to improve the mental health of human service workers.…”
mentioning
confidence: 61%
“…This educational process is considered to enhance objective thinking of one's self and to prevent the creation of a firm belief in a self-image of being an inexhaustible and super-competent person; one of the reasons for burnout 32) . West et al indicated that the EE and PA had improved significantly four months after the stress management course which had included training in assertive skills through role-playing 17) . In the CS-list, two communication skills, "accepting valid criticisms" and "negotiation", of the intervention improved significantly after the AsT.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether 11 of the 19 included studies (30,35,37,38,(42)(43)(44)(45)(46)(47)(48) had interventions that were specifically directed towards nurses. In seven studies (32-34, 36, 39, 49, 50), interventions were directed at all of the staff of participating health care facilities, and, in one study, the intervention was directed towards respiratory therapists (40).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…No randomized controlled studies were found that evaluated the therapy or guidance of employees with burnout, but several controlled studies evaluated intervention among a working population with a burnout measure as the dependent variable (17)(18)(19)(20)(21)(22)(23)(24)(25). However, none of the studies concerned patients diagnosed with burnout.…”
Section: Classification In Guidelinesmentioning
confidence: 99%